SHARI’A COMPLIANCE PRINCIPLES IN FINANCIAL TECHNOLOGY - Ishak Ishak; Ilham Ilham; Akbar Sabani (Jurnal Cendekia Hukum, 2022)
Currently in Indonesia, financial technology (fintech) services have developed rapidly. The development of fintech in Indonesia has been responded positively by several regulations issued by the Financial Services Authority (OJK) and Bank Indonesia (BI). In addition to conventional fintech, sharia fintech in Indonesia has also begun to develop significantly, especially since the DSN-MUI fatwa on Sharia Information Technology-Based Financing Services (Fatwa No.117/DSN-MUI/IX/2018). Although sharia fintech has begun to develop, OJK has not fully accommodated the DSN-MUI Fatwa as a binding regulation. The DPS institution as a supervisor for Islamic financial institution entities as well as for start-ups such as fintech that operates according to sharia must follow the regulations that have been decided by the DSN-MUI so that these entities can operate in sharia and this is part of compliance with sharia compliance). This study investigates the Shariah compliance status of financial technology services. The research method used is the library research method with a literature review approach. The results of the study show that currently fintech operating in sharia still needs stronger legal instruments so that compliance with sharia is truly carried out comprehensively and not only applies a kind of label that is run by sharia, so that the existence of fintech and customer trust (consumers can be maintained.